MENINGKATKAN KEUANGAN RUMAH TANGGA: MENGGALI JIWA WIRAUSAHA TANPA BATAS USIA - Puspita, Wulan Dri; June, Cindy Getah Trisna; Santi, Fitriana; Lakaq, Maria Charolina Ina (STKIP Persada Khatulistiwa Sintang, 2023)
ABSTRACTEntrepreneurship is one form of self-reliance that is currently being fostered by the government. Efforts to become a developed nation are ongoing through various programs. One of the programs currently implemented is the Family Hope Program (Program Keluarga Harapan or PKH). This initiative aims to enable families to stand on their own by creating new entrepreneurs within beneficiary families. Based on observations, it is known that many of the beneficiary families are interested in and have even started their own businesses. The problem lies in the lack of strong motivation among these entrepreneurs or potential entrepreneurs. Community service programs are carried out with the goal of providing training on the benefits of entrepreneurship and successful strategies to overcome challenges. The results of these activities show that groups of mothers are becoming motivated to start their own businesses as they understand the meaning and benefits of entrepreneurship.Keywords: motivation, entrepreneurship, mothers, PKH groupsÂ ABSTRAKWirausaha adalah salah satu bentuk jiwa mandiri yang saat ini sedang dibentuk oleh pemerintah. Upaya untuk menjadi negara maju terus dilakukan melalui berbagai program. Salah satu program yang saat ini dicanangkan adalah Program Keluarga Harapan (PKH). Bentuk usaha memberikan kemampuan untuk bisa berdiri sendiri dengan menciptakan wirausaha baru di kelompok keluarga penerima bantuan. Berdasarkan hasil observasi diketahui bahwa banyak diantara keluarga penerima bantuan yang minat bahkan sudah memulai usaha. Permasalahannya adalah dari pelaku usaha atau calon wirasuaha tidak memiliki motivasi tangguh. Program pengabdian masyarakat dilakukan dengan tujuan memberikan pelatihan mengenai manfaat berwirausaha dan kiat sukses menghadapi tantangan. Hasil dari kegiatan menunjukkan bahwa kelompok ibu-ibu mulai tergugah untuk memulai wirausaha karena memahami makna dan manfaat dari berwirausaha.Kata Kunci: motivasi, wirausaha, ibu-ibu, kelompok PKH